YIIFSWA II OPENDAY - Interview with Saleh Ahmed - International Institute of Tropical Agriculture (2019)
Interview with Saleh Ahmed, a seed grower in Nigeria. YIIFSWA-II showcases High Ratio Propagation Technologies and demonstrates large scale production of early generation seed yam.